The Application of Numerical Study for Dynamic Vibration Absorber in Suspension System to Improve Four Wheel Vehicle Comfort - Hafizah, Hafizah; Mainil, Rahmat Iman; Nazaruddin, Nazaruddin; Abdurrahman, Ridwan (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
This study aims to develop a Dynamic Vibration Absorber (DVA) for a four-wheeled vehicle, specifically the